Komunikasi Antar Budaya Studi Fenomenologisantara Masyarakat Timor Timur Dan Masyarakat Musi Di Desa Mangan Jaya Kecamatan Muara Kelingi - Subehan Subehan; Rama Wijaya Kesuma Wardanni (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2023)
This type of research is qualitative research with the approach used is phenomenology. In this study, researchers interviewed community leaders who understood the meaning of events or incidents of conflict between the people of East Timor and the Musi people in Mangan Jaya Village in recent years showing encouraging changes Adaptation Between the East Timorese and Musi Communities in Mangan Jaya Village, Muara Kelingi District, another thing that also shows an attitude of openness between the East Timorese and Musi people is the creation of harmonious economic relations, they shop with each other and other economic transactions are carried out well. The people of East Timor and the people of Musi showed a positive attitude with the open acceptance of each community group. This can be seen from the fact that there is no difference in treatment between the Musi group and the East Timorese.